Processos fonográficos e música de tradição oral em Pernambuco - Sonoda, Andre Vieira (2008)
Throughout the twentieth century audio technology has contributed greatly to the development of ethnomusicology. Initially with the creation of the phonograph and techniques of sound recording, enabling the development of phonographic archives and later with creation of technologies that provide better sound quality, lower cost and more appropriate concepts to new paradigms of the discipline, even knowing that until the middle of the twentieth century ethnomusicology not had this name, scientific approach or methodological orientation. Despite the important contribution of audio technology for ethnomusicology, seem that phonographic processes can influence the results of acoustic musical traditions recorded. This study attempts to understand how different concepts and procedures of production music can influence the acoustic outcome of the sound recordings and, consequently, the musical-aesthetic structure of events transmitted by oral tradition in the state of Pernambuco. Thus, it is composed of bibliographic research on the main scientific productions of audio technology in ethnomusicology, field research with techniques of interviews, questionnaires and direct observation of contexts and important people in music production and oral tradition music in the State. Another important aspect for research was the experience gained over many years of work in ethnomusicology and audio technology, in addition to daily work in the Centro de Difusão e Realizações Musicais SESC - Casa Amarela (PE - Brasil) aimed mainly to Brazilian classical music and Brazilian oral tradition music. This study showed that the phonographic production process can influence the acoustic outcome of oral tradition music, providing differences between the sound of performance context and the sound recorded on media. Inappropriate concepts for the production of this type of music seems to contribute, indirectly, to the occurrence of changes in social structures of these events. Thus, the phonographic processes constitute an important topic of study for ethnomusicology calling attention to issues of changes in music after a production process beyond show gaps in the discipline about issues of power and relevance related to music production. Finally, it was possible to conclude that physical or conceptual factors in the production process of the oral tradition music influence it, sometimes in irreversible form in both artistic and cultural as socio-political and philosophical point of view.